1969
DOI: 10.1111/j.1460-2466.1969.tb00846.x
|View full text |Cite
|
Sign up to set email alerts
|

A Primacy Effect in Decision-Making by Jurors

Abstract: An experiment varied the order of presentation of ostensible trial testimony. Prior to the reading of strong final evidence from the prosecution, 65 university students taking the role of jurors read other arguments which were identical for all recipients except that they came from either ( a ) the prosecution first and the defense second or ( b ) the defense first and the prosecution second. Two tentative verdicts and a final verdict were marked anonymously following the respective presentations.The sequence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

1975
1975
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 0 publications
0
11
0
1
Order By: Relevance
“…Similarly, in multiple-choice tasks, in which opinion is based on one-shot experience per option, such as in wine tasting, the first option is more likely to be chosen (Mantonakis et al, 2009). Although the relation between the above examples of primacy and outcome primacy is unclear, we hypothesize that outcome primacy and primacy in belief-updating tasks , such as jurors' decision after a sequence of argumentative speeches or the stating of a personality impression after a sequence of words describing personality traits (Asch, 1946; Cromwell, 1950; Lund, 1925; Peterson & DuCharme, 1967; Stone, 1969), can be explained using a similar theoretical framework.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in multiple-choice tasks, in which opinion is based on one-shot experience per option, such as in wine tasting, the first option is more likely to be chosen (Mantonakis et al, 2009). Although the relation between the above examples of primacy and outcome primacy is unclear, we hypothesize that outcome primacy and primacy in belief-updating tasks , such as jurors' decision after a sequence of argumentative speeches or the stating of a personality impression after a sequence of words describing personality traits (Asch, 1946; Cromwell, 1950; Lund, 1925; Peterson & DuCharme, 1967; Stone, 1969), can be explained using a similar theoretical framework.…”
Section: Discussionmentioning
confidence: 99%
“…As the Coleman (1968) epigraph suggests, the observation of the changes of beliefs over time should provide all the information about the causal relations between message variables and belief change. For example, the effect of order of message presentation on belief change (e.g., primacy vs. recency; Hovland et al, 1957; Stone, 1969) can be observed merely by looking at the final belief position; however, the process by which the belief changes can be more clearly revealed by its over‐time trajectory, in which the way that the belief changes in response to each piece of message information and in response to cognitive processing may be assessed. Despite its importance, the time course of belief change is little known.…”
mentioning
confidence: 99%
“…In contrast, recency effects arise when the last piece of information in a sequence is more influential than the preceding information in persuasion. Empirical work has provided evidence supporting both primacy and recency effects in a wide range of research contexts (e.g., Cromwell, 1950; Hovland & Mandell, 1957; Stone, 1969). However, disagreement exists over which of the two effects is more likely to appear (Hogarth & Einhorn, 1992).…”
Section: Literature Reviewmentioning
confidence: 99%